Women and Terrorism: Hegemony of Patriarchal Culture and Poverty as Drivers of Terrorism Action by Women - Muhammad Arif Mustaqim, (Advances in Humanities and Contemporary Studies, 2022)
Poverty is not only interpreted as economic poverty but also has wider problems. Economic poverty can be only overcome if poverty in other various aspects of life is also overcome. Poverty is very close to women because women are more vulnerable to impoverishment, especially structural impoverishment. This is because women are marginalized in political, economic and social spaces. Women become helpless due to the hegemony of patriarchal culture and repressive social structures. So that women tend to accept injustice in their position as part of society. In the end, impoverishment of women as a result of the hegemony of patriarchal culture actually contributed to the involvement of women in terrorist activities in various regions of Indonesia, for example, suicide bombings in Surabaya some times ago.